Marcas da violência e jogos do poder no romance urbano de Patrícia Melo - Cláudia Castanheira (Estudos de Literatura Brasileira Contemporânea)
This work analyzes the romance O Matador (The Killer) by Patrícia Melo. Its thematic universe and discursive strategies break not only with the prospects of the more contemporary feminist literary criticism, but also with the bourgeois ideological system, more broadly. The object is to highlight how the use of the male voice and masculine cultural experiences, taken to its ultimate consequences, may be converted into a subliminal criticism regarding the ways of how the discriminating speeches are built, through sexual, economic and social criteria in our society.